G-CSF as a suitable alternative to GM-CSF to boost dinutuximab-mediated neutrophil cytotoxicity in neuroblastoma treatment. Issue 5 (28th May 2021) - Martinez Sanz, Paula; van Rees, Dieke J; van Zogchel, Lieke M J; Klein, Bart; Bouti, Panagiota; Olsman, Hugo; Schornagel, Karin; Kok, Ivana; Sunak, Ali; Leeuwenburg, Kira; Timmerman, Ilse; Dierselhuis, Miranda P; et al.
Abstract : Background: Current immunotherapy for patients with high-risk neuroblastoma involves the therapeutic antibody dinutuximab that targets GD2, a ganglioside expressed on the majority of neuroblastoma tumors. Opsonized tumor cells are killed through antibody-dependent cellular cytotoxicity (ADCC), a process mediated by various immune cells, including neutrophils. The capacity of neutrophils to kill dinutuximab-opsonized tumor cells can be further enhanced by granulocyte-macrophage colony-stimulating factor (GM-CSF), which has been shown in the past to improve responses to anti-GD2 immunotherapy. However, access to GM-CSF (sargramostim) is limited outside of Northern America, creating a high clinical need for an alternative method to stimulate dinutuximab responsiveness in the treatment of neuroblastoma. In this in vitro study, we have investigated whether clinically well-established granulocyte colony-stimulating factor (G-CSF) can be a potentially suitable alternative for GM-CSF in the dinutuximab immunotherapy regimen of patients with neuroblastoma. Methods: We compared the capacity of neutrophils stimulated either in vitro or in vivo with GM-CSF or G-CSF to kill dinutuximab-opsonized GD2-positive neuroblastoma cell lines and primary patient tumor material. Blocking experiments with antibodies inhibiting either respective Fc gamma receptors (FcγR) or neutrophil integrin CD11b/CD18 demonstrated the involvement of these receptors in the process of ADCC. Flow cytometry and live cell microscopy were used to quantify and visualize neutrophil-neuroblastoma interactions. Results: We found that G-CSF was as potent as GM-CSF in enhancing the killing capacity of neutrophils towards neuroblastoma cells. This was observed with in vitro stimulated neutrophils, and with in vivo stimulated neutrophils from both patients with neuroblastoma and healthy donors. Enhanced killing due to GM-CSF or G-CSF stimulation was consistent regardless of dinutuximab concentration, tumor-to-neutrophil ratio and concentration of the stimulating cytokine. Both GM-CSF and G-CSF stimulated neutrophils required FcγRIIa and CD11b/CD18 integrin to perform ADCC, and this was accompanied by trogocytosis of tumor material by neutrophils and tumor cell death in both stimulation conditions. Conclusions: Our preclinical data support the use of G-CSF as an alternative stimulating cytokine to GM-CSF in the treatment of high-risk neuroblastoma with dinutuximab, warranting further testing of G-CSF in a clinical setting.